Introduction of medicinal plants of the familyRosaceae Juss. of the Natural Flora of Northern Tien Shan - Yerekeyeva, S.Zh.; Arysbayeva, R.B.; Musrat, A.; Orloci, Laszlo; Bazarbayeva Т.А.; Mukanova, G.A. (Fundamental and Experimental Biology, 2021)
Rosaceae Juss. family have more cosmopolitan plants growing in many parts of the globe. Apart from food and decorative plants, there are also medicinal plant species. Increasing the potential of the use of medicinal plants currently represents one of the top-priority objectives that requires a comprehensive study of plants in isolation from natural flora, growing and preserving the species. The article focuses on Kazakhstani plant species of the Rosaceae Juss. family, and specifics of their growth and distribution. Endangered species, as reported in the literature and online sources, are briefly described. Also, the specifics of introducing 30 plant species of family Rosaceae Juss. from global and Kazakhstan flora in the Main Botanic Garden of Almaty are described, introduction parameters (phenological observation and seed quality parameters) are analyzed for 7 medicinal plant species (Agrimonia asiatica Juz., Filipendula ulmaria(L.) Maxim., Filipendula vulgaris Moench, Potentilla argentea L., Potentilla recta L., Fragaria vesca L., and Fragaria viridis (Duch.) Weston) are introduced from the Northern Tien Shan flora, and a brief summary of the introduction details obtained on the basis of the successful introduction index is provided.